PARAMETERS OF HOTSPOTS AND THERMOCHEMICAL PLUMES DURING THEIR ASCENT AND ERUPTION - Dobretsov N.L.; Kirdyashkin A.A.; Kirdyashkin A.G.; Gladkov I.N.; Surkov N.V. (My University, 2006)
Thermochemical plumes develop at the core-mantle boundary in the presence of a heat flow from the outer core and at local chemical doping that decreases the melting temperature near the bottom of the lower mantle (this dope triggers the melting of the mantle material and the ascent of the plume). The paper presents evaluations for the heat power of the Hawaiian and Iceland plumes and the results of the experimental modeling of a thermochemical plume. The diameter of a plume conduit was determined to remain virtually unchanging in the course of plume ascent. When the top of a plume reaches a "refractory" layer, whose melting temperature is higher than the melt temperature in the plume conduit, a mushroom-shaped head of the plume develops beneath the bottom of this layer. The analysis of geological and geophysical data and the results of experimental modeling are used to develop a thermal physical model for a thermochemical plume. The balance relations for the mass and thermal energy and systematic tendencies in the heat and mass transfer during free convection were utilized to derive a system of equations for the heat and mass transfer of a thermochemical plume. Parameters were determined for a thermochemical plume ascending from the core-mantle boundary. Geodynamic processes are considered that occur during the ascent of a plume before it reaches the surface. The effect of the P-T conditions on the shape and size of a plume roof is analyzed, and a model is proposed for mass transfer between a thermochemical plume and the lithosphere, when the plume reaches the bottom of a "refractory" layer in the lithosphere. © Pleiades Publishing, Inc., 2006.